Springs, streams and spas of London history and associations - Foord, Alfred Stanley (Frederick A. Stokes, 1910)
This title is divided into sections dealing with: streams and spas north of the Thames; streams and spas south of the Thames; conduit system of water-supply; and an appendix on shallow or surface wells, and pumps of London.